Community : the structure of belonging - Block, Peter, 1939- (BK life book., 2008)
Offers an exploration of the exact way community can emerge from fragmentation. This book explores a way of thinking about our places that creates an opening for authentic communities to exist and details what each of us can do to make that happen. It shows us how we can overcome isolation and anxiety and create communities alive with energy.